A hybrid numerical model for simulating aero-elastic-hydro-mooring-wake dynamic responses of floating offshore wind turbine. (15th January 2023) - Yu, Ziying; Ma, Qingwei; Zheng, Xing; Liao, Kangping; Sun, Hanbing; Khayyer, Abbas
Abstract: It demands many computational resources to model the coupled responses of a floating offshore wind turbine (FOWT), especially for its aero-elastic-hydro-mooring-wake dynamics and their interaction. In this paper, a new hybrid numerical model for FOWT systems is developed, which is based on the hybrid potential-viscous flow model called qaleFOAM. In this model, the aerodynamics of wind turbine are solved by the unsteady actuator line method (UALM); the elastic responses of the turbine blade are calculated by the Legendre spectral finite element model (BeamDyn); the hydrodynamics of the floating platform are dealt with by the combination of the fully nonlinear potential solver and a two-phase Navier–Stokes solver; the mooring dynamics are considered with the Lumped Mass Mooring Model (MoorDyn), and the turbine wake is solved with the large eddy simulation (LES) model. This newly formulated model can deal with wind, wave, mooring dynamics, platform motions, and turbine structural dynamics involved in the FOWT system. To demonstrate the capability of the present model, various cases with different complexities are investigated and compared with the experimental data and other numerical results. Then, the model is applied to simulation of a semi-submersible FOWT system, subjected to a regular wave and a uniform wind. The prediction of the aerodynamic performance, blade tip deflection, platform motion responses, and mooring line tension loads show good agreements with the results from other methods. In addition, the phenomenon of the coupled effects between the dynamic responses of platform, blade deformation and wake flow are captured reasonably well. Highlights: A new hybrid numerical model for FOWT systems is developed by combining qaleFOAM with ALM code, BeamDyn and MoorDyn. The aerodynamic loads, blade tip deflections, mooring dynamics, dynamic responses of the FOWT and its wake are investigated. A satisfactory computational robustness of the present model is achieved.